A checklist of ferns and lycophytes from Marai-Parai in Kinabalu Park, Sabah - Florina Anthony; Andi Maryani A. Mustapeng; Scholastica Lanting; Wong Haoen; Monica Suleiman (Sabah Parks Nature Journal, 2024)
Mount Kinabalu's unique ecosystem supports a high diversity of rare and endemic fern species, yet the species richness of ferns and lycophytes in the Marai-Parai region remains understudied. This research aimed to investigate and document the species richness of ferns and lycophytes in the Marai-Parai area of Kinabalu Park, Sabah. Using existing identification resources and herbarium collections, a total of 62 species from 16 families were identified, including 55 ferns and seven lycophytes. Oreogrammitis (six spp.) and Hymenophyllum (five spp.) were the most diverse genera, while lycophytes were represented by Lycopodiaceae (five species) and Selaginellaceae (two species). These findings contribute valuable information on fern and lycophyte diversity within the biodiverse Kinabalu Park, aiding conservation efforts by identifying areas of high diversity and potential endemism, and guiding future management strategies